ANALYSIS OF THE LOW UTILIZATION OF MOBILE JKN ADOPTION FOR PATIENT REGISTRATION AT DUMAI GENERAL HOSPITAL IN 2025 - Badriyana, Suci; Leonita, Emy; Kiswanto, Kiswanto; Renaldi, Reno; Jepisah, Doni (HEARTY, 2026)
Digital transformation in healthcare has become a major focus of the Indonesian government through the development of the Mobile JKN application by BPJS Kesehatan. However, at Dumai General Hospital (RSUD Dumai), the utilization rate of this application remains low. This study aims to analyze the factors contributing to the low adoption of Mobile JKN in patient registration using the Innovation Resistance Theory (IRT) by Ram and Sheth (1989), which includes five dimensions: Usage Barrier, Value Barrier, Risk Barrier, Tradition Barrier, and Image Barrier. The research applied a qualitative case study approach involving key informants consisting of both users and non-users of Mobile JKN, as well as hospital registration staff. Data were collected through in-depth interviews and field observations, then analyzed thematically. The findings show that low adoption is influenced by limited digital literacy among elderly patients (Usage Barrier), perceptions that manual registration is faster (Value Barrier), concerns about data security and technical issues (Risk Barrier), strong preference for face-to-face interactions (Tradition Barrier), and the negative image of the application due to system errors and insufficient socialization (Image Barrier).